(untitled) - Kothari, D P. (Boston, 2008)
Modern Power System Analysis is one of the most current Power Systems texts available, incorporating MATLAB and SIMULINK. In simple, straightforward language, the book provides a modern introduction to power system operation, control and analysis. With up-to-date chapters on power system security, load forecasting, and voltage stability, Modern Power System Analysis offers a well-priced alternative to older, more expensive texts. The text includes helpful pedagogy such as numerous figures and a wide variety of exercises and solved examples.Written with a global perspective and presenting the latest in technological advances, these books will give students of all backgrounds a solid foundation in key engineering subjects.
Keywords: Electric power systems,Hệ thống điện